Pemberdayaan Peternak Anggota BUMDESA melalui Optimalisasi Produksi dan Digital Marketing di Desa Bringin, Tuban - Lia Nur Aini; Teguh Dwi Putra; Afsah Indah Maulidah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The community service program from Politeknik Pertanian dan Peternakan Mapena 2024 aims to help improve the economy of the people of Bringin Village, Montong District, Tuban, particularly the member farmers of BUMDesa Suryonegoro Bringin Village by optimizing the production and digital marketing of goat and sheep rearing. Goat and sheep rearing in the Bringin Village community are sideline activities that are conventionally carried out. This program aims to help farmers increase their income through good and correct husbandry practices and increase livestock sales through the use of social media. The range of program activities includes extension, livestock health checks, and training. The farm optimization extension activities covered good goat and sheep husbandry techniques, understanding the livestock recording system, feed management, and livestock health management. Digital marketing extension activities provided participants with the knowledge to use social media as a marketing tool, such as Instagram. Farmers who are members of BUMDesa are also provided with training to support the livestock maintenance process to be more optimal, such as silage making techniques, urea molasses blocks, and the use of livestock manure waste as black soldier fly (BSF) maggot culture media. At the end of the program, a focus group discussion was held with stakeholders such as the Indonesian Goat and Sheep Breeders Association (HPDKI) of the Tuban region, the Tuban Food Security, Agriculture and Fisheries Office, and the philanthropic institution, Nurul Hayat to support the sustainability of the program.